Evaluating the brand image of a rock festival using positive critical incidents. Issue 2 (5th June 2017) - Kinnunen, Maarit; Uhmavaara, Kerttu; Jääskeläinen, Maiju
Abstract : Purpose: Since effective and successful branding increases the popularity and loyalty of the festival, and its economic success factors like positive media coverage and sponsors' interest, it is essential that the festival brand image is credible and strong. The purpose of this paper is to focus on interpreting audience's perceptions on a rock festival brand image to find out the factors that influence the brand image of the festival and how organisers could contribute to it. Design/methodology/approach: Critical Incident Technique (CIT) was used in defining the factors influencing a rock festival brand. Findings: The attending public co-produce the festival brand, and the brand image was created by the festival community where the importance of social and inclusive behaviour towards strangers was essential. Research limitations/implications: The data were collected as a voluntary response sample which led to a biased sample. Another limitation is that the informants were asked to describe only positive incidents. Practical implications: The festival brand image cannot be produced solely by organisers; rather, volunteers, artists and especially audience members are crucial for the success and creditability of the brand. This should be considered in marketing and event management. Originality/value: The use of CIT in the festival brand image evaluation introduces new possibilities in the field.